A moderated mediation model of whistleblowing in the hotel industry - Aslam, Muhammad Kashif; Rescalvo-Martin, Elisa; Karatepe, Osman M.; Akhtar, Muhammad Waheed; Azhar, Muhammad Salman (Elsevier Sci Ltd, 2026)
Drawing on the motivational information processing theory, our paper developed and tested a moderated mediation model of whistleblowing. Specifically, our paper tests: (1) the effect of perceived overqualification (POQ) on whistleblowing intention; (2) prosocial motivation as a mediator between POQ and whistleblowing intention; (3) high involvement work practices (HIWPs) as a moderator between POQ and whistleblowing intention; and (4) HIWPs as a moderator of the influence of POQ on said outcome via prosocial motivation. The results from the partial least squares structural equation modeling suggest that overqualified employees who are pro-socially motivated display proclivity to whistle blow. More importantly, HIWPs strengthen the positive impact of POQ on propensity to whistle blow via prosocial motivation such that this positive impact is stronger among employees high on HIWPs than employees low on HIWPs. All the hypothesized links were corroborated, and the research model proposed in this paper was viable.
Keywords: High involvement work practices; Hotel employees; Perceived overqualification; Prosocial motivation; Whistleblowing intention